2016
DOI: 10.1007/s10265-016-0786-3
|View full text |Cite
|
Sign up to set email alerts
|

The grapevine VviPrx31 peroxidase as a candidate gene involved in anthocyanin degradation in ripening berries under high temperature

Abstract: Anthocyanin levels decline in some red grape berry varieties ripened under high-temperature conditions, but the underlying mechanism is not yet clear. Here we studied the effects of two different temperature regimes, representing actual Sangiovese (Vitis vinifera L.) viticulture regions, on the accumulation of mRNAs and enzymes controlling berry skin anthocyanins. Potted uniform plants of Sangiovese were kept from veraison to harvest, in two plastic greenhouses with different temperature conditions. The low te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
124
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 63 publications
7
124
0
2
Order By: Relevance
“…Several authors reported that the loss of anthocyanin synthesis following HT is due to the reduced expression of anthocyanin biosynthetic genes (Yamane et al, 2006; Azuma et al, 2012; Lecourieux et al, 2017). Sometimes, however, despite a sharp reduction in terms of anthocyanin concentration, a concomitant reduction in anthocyanin biosynthetic genes expression was not found, as reported for Muscat Hamburg berries on fruiting cuttings (Carbonell-Bejerano et al, 2013) and in Cabernet Sauvignon and Sangiovese vines grown under increasing temperature (Mori et al, 2007; Movahed et al, 2016). In these cases, also an involvement of anthocyanin degradation, implying the action of peroxidases should be hypothesized (Mori et al, 2007; Movahed et al, 2016) as it was previously seen in other plant species, as Brunfelsia flower petals (Vaknin et al, 2005), litchi (Zhang et al, 2005), and strawberry fruits (Chisari et al, 2007).…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Several authors reported that the loss of anthocyanin synthesis following HT is due to the reduced expression of anthocyanin biosynthetic genes (Yamane et al, 2006; Azuma et al, 2012; Lecourieux et al, 2017). Sometimes, however, despite a sharp reduction in terms of anthocyanin concentration, a concomitant reduction in anthocyanin biosynthetic genes expression was not found, as reported for Muscat Hamburg berries on fruiting cuttings (Carbonell-Bejerano et al, 2013) and in Cabernet Sauvignon and Sangiovese vines grown under increasing temperature (Mori et al, 2007; Movahed et al, 2016). In these cases, also an involvement of anthocyanin degradation, implying the action of peroxidases should be hypothesized (Mori et al, 2007; Movahed et al, 2016) as it was previously seen in other plant species, as Brunfelsia flower petals (Vaknin et al, 2005), litchi (Zhang et al, 2005), and strawberry fruits (Chisari et al, 2007).…”
Section: Introductionmentioning
confidence: 65%
“…Intriguingly, other studies suggested a cultivar-dependent thermal response of acidity and pH (Bergqvist et al, 2001; Sadras et al, 2013a,b; Movahed et al, 2016). …”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations